Konsep Kesempurnaan Hidup Menurut Aliran Kepercayaan dan Tasawuf - Purba, Fitri Huril Aini (YASIN, 2023)
Every human being wants to do the best in his life, so it’s no wonder that there are many people who do various activities (worship) to God in order to get a perfect life. When talking about the perfection of life, it will refer to the perpetrators who live life itself, namely humans. Human desires in achieving a perfect life then give birth to various kinds of beliefs which are then used as a bridge in achieving goals. This research uses library research. This research uses phenomenological methods. This study uses a comparative approach, researchers use data analysis techniques in the form of content analysis (content analysis) library research where the data source is in the form of books and documents as well as literature in other forms to provide input and transformative thoughts about the concept of perfection of life according to the flow of belief so as to provide clearer information to others, especially on the point of view of Sufism on the concept. Based on the findings of this study, it is that the difference in the meaning of the perfection of life between the teachings of Sufism and the flow of belief is that in the flow of belief the perfection of life means perfecting life from all desires and uniting with God through the practice is carried out meanwhile, in Sufism Perfection of Life is actually located in how high the level of servitude of a servant to God. Hasan Al-Bashri is a well-known Sufi who pioneered zuhud. According to his view, the path to the highest level of perfection (Ma’rifat) is by leaving worldly pleasures, through the path of Al-Khauf Wa Al-Raja’ as the main tariqah to become a Sufi. Soenarto’s view in the teachings of Paguyupan Ngesti Tunggal, in order to achieve Perfection in life, there are eight teaching concepts that must be followed by their followers as the foundation of life to achieve happiness. The eight concepts are called Hastasila, which is divided into 2 namely Trisila and Pancasila.